Reading Speed Effectiveness in Improving Literary Culture in the Industrial Revolution 4.0 - Hilmi, Indah Fajri; Alwi, Nur Azmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThe current era of the industrial revolution 4.0 is increasingly sophisticated which is characterized by the rapid development of technology and information in all aspects of the field. In responding to the industrial revolution 4.0 era, literacy skills taught since elementary school are aimed at building a superior generation, where technology and information become more sophisticated. This article discusses Reading Speed Effectiveness (RSE) in improving literacy culture in Elementary Schools. The ability to read is the main capital in personal life, especially in the school environment. In school life, reading ability is very necessary, because if students do not have adequate reading skills, especially in fast reading, these students will experience difficulties in learning, because speed reading is very beneficial for readers to read a discourse with minimal time and balanced with maximum content comprehension. Speed reading is a combination of speed reading skills with the ability to reading comprehension.AbstrakEra revolusi industri 4.0 saat ini sudah semakin canggih yang ditandai dengan perkembangan pesat teknologi dan informasi di segala aspek bidang. Dalam menyikapi era revolusi industri 4.0, kemampuan literasi yang diajarkan sejak sekolah dasar bertujuan untuk membangun generasi yang unggul, di mana teknologi dan informasi semakin canggih. Artikel ini membahas tentang efektifitas kecepatan membaca untuk meningkatkan budaya literasi di Sekolah Dasar. Kemampuan membaca merupakan modal utama dalam kehidupan pribadi, terutama di lingkungan sekolah. Dalam kehidupan sekolah, kemampuan membaca sangat diperlukan karena ketika siswa tidak memiliki kemampuan membaca yang memadai terutama dalam membaca cepat, siswa tersebut akan mengalami kesulitan dalam belajar, karena membaca cepat sangat bermanfaat bagi pembaca untuk membaca sebuah wacana dengan waktu yang minimal dan diimbangi dengan pemahaman isi yang maksimal. Membaca cepat merupakan perpaduan antara kemampuan membaca cepat dengan kemampuan membaca pemahaman.